Language and the conception of reality - John Gabriel Mendie; Stephen N Udofia (International Journal of Humanities and Innovation (IJHI), 2019)
There is a widespread belief that language is a veritable instrumentum laborat (working tool) for the communication of thoughts and the conception of reality. There is equally a lingering belief that language pictures or mirrors reality. Nevertheless, to what extent can we authenticate this existing opinion? Is it the case that the conglomerate of reality can be represented linguistically without any iota of defect/fallibilism? Can language mirror reality perfectly as it is, in itself? What really is the ontological status of language? What is language anyway? How does it relate to the world? How does it relate to the mind? Should our view of language influence our view of the world? Even more seriously, what is the limit of language in the herculean task of conceiving and revealing reality? Armed with the concerns highlighted above, this paper, attempts to grapple with these questions, by first seeking insights into the meaning, nature and use of language; the nature of reality; and the role of language within the context of effective representation and a veridical a fortiori conception of different ‘forms of life and states of affairs’ of reality.